DAMPAK SISTEM PEMBATASAN KUOTA TERDIFERENSIASI BERBASIS NFC DAN TRANSPARANSI TRANSAKSI TERHADAP PERILAKU KONSUMSI SANTRIWATI DI PP DARUSSALAM PUTRI SELATAN - Khafidhotus Sholikhah; Dawimatus Sholihah (Universitas KH. Mukhtar Syafaat, 2025)
This study analyzes the impact of a differentiated spending quota system and transaction history transparency based on NFC technology on female students' consumption behavior at Darussalam Putri Selatan Islamic Boarding School. Using a descriptive qualitative approach with a case study method, data were collected through in-depth interviews with 11 informants, 14 days of participatory observation, and documentation study. The findings reveal that spending quotas effectively reduce impulsive purchasing but trigger